PERANCANGAN POINT OF SALES DESKTOP USAHA KECIL DENGAN PRINTER DAN BARCODE SCANNER - Alvina Leony; Saut Pintubipar Saragih (Universitas Putera Batam, 2026)
This study focuses on designing and building a desktop-based Point of Sales system with inventory management that supports transactions in small businesses, specifically for in this paper, the I.M Store using Visual Studio, VB.NET and MySQL as well as UML. This system is integrated with a barcode scanner and a thermal printer to support sales processing. An iterative software development approach with steps such as: requirements, design and development, testing and evaluation were used to ensure that the system is designed and developed according to the stores documented needs. The system is designed to support three user roles, namely the administrator, cashier, and employee, each with different access rights. The developed application allows the administrator to manage master data and reports as well as backup and restore feature, for cashiers to process sales and return submissions due to buyer complaints to the administrator, and for employees to manage pickup and delivery sales as well as return submissions for problematic products at the store to the administrator. Evaluation results show that the system operates correctly and fulfills the operational needs in Store I.M. This research concludes that a desktop-based POS system can be used to support small business operations